Влияние духовно-эстетического воспитания на развитие личности в процессе образования - Абдурахманова, А.Т (SCIENCE and SOCIETY, 2020)
The state pays great attention to young people, has determined as a priority of state policy, defined the tasks of forming the spiritual and aesthetic education of the future generation. In teaching , it is an important factor in educating students in the spiritual, moral and
Keywords: education; upbringing; training; priorities in politics; spirituality; morality; aesthetics